Os sentidos da proteção social: um estudo a partir das famílias beneficiárias do Programa Bolsa Família no município de João Pessoa/PB - Silva, Roberta Teodorico Ferreira da (2018)
The present dissertation study entitled- The senses of social protection: a study from the families benefiting from the Bolsa Família Program in the city of João Pessoa / PB, aims to problematize the senses of social protection from the perception of beneficiary families from the Bolsa Família Program in the municipality of João Pessoa/PB. This study was based on the hypothesis that income transfer programs, especially the Bolsa Família Program, have insufficient income security to guarantee the protective capacity of families, including in terms of the effectiveness of conditionalities imposed on families. The investigative process was based on a qualitative exploratory and descriptive approach based on the use of secondary data provided by the Research - Protective Capacity of Beneficiary Families database in Paraíba State, developed by the Center for Studies and Research in the State of Paraíba. Scope of the Casadinho/Procad Project (2011-2016). For the study, the territorial clipping of the city of João Pessoa/PB was defined, defined as the largest urban center of the State of Paraíba and for presenting the largest number of interviewed families (545) according to the referred research. Thus, the methodological approach was based on the following indicators: profile of respondents; relationship services and benefits; respondents' perceptions and senses of social protection, highlighting the ways in which they feel protected. Thus, the profile of families is of people who are in poverty, with precarious work and informal ties, low education and minimal exit conditions from the poverty cycle. The results point, first, to the importance of the benefit of the PBF for families, as a guarantee of exiting extreme poverty; On the other hand, there is no coverage of services in the territory of housing that guarantees access to families and compliance with conditionalities. Thus, despite being a welfare benefit, there is a large absence of monitoring of families by the social and social network, as it is respondents wanted to receive an operative technical visit. This can also be demonstrated by the lack of knowledge of the social-service network by the interviewed families. However, the study is presented as an indispensable element, since it intends to identify elements that can contribute to the debate and strengthening of the Public Policies of Social Protection from the perspective of affirmation of the law, especially in the relationship non-contributory social protection and income security.